Photocatalytic Degradation of Inherent Pharmaceutical Concentration Levels in Real Hospital WWTP Effluents Using g-C3N4 Catalyst on CPC Pilot Scale Reactor - Ilaeira Rapti; Theodora Kourkouta; Evrydiki-Maria Malisova; Triantafyllos Albanis; Ioannis Konstantinou (Molecules, 2023)
The objective of this work was to evaluate the efficiency of a solar photocatalytic process using g-C3N4 as photocatalyst on the degradation of pharmaceutical compounds detected in hospital wastewater treatment plant secondary effluents. A compound parabolic collector pilot plant, established in the secondary effluent stream of the Ioannina city hospital wastewater treatment plant, was used for the photocatalytic experiments. The analysis of the samples before and after the photocatalytic treatment was accomplished using solid phase extraction (SPE), followed by UHPLC-LTQ/Orbitrap HRMS. Initial effluent characterization revealed the presence of ten pharmaceutical compounds. Among these, amisulpride, O-desmethyl venlafaxine, venlafaxine and carbamazepine were detected in all experiments. Initial concentrations ranged from 73 ng L−1 for citalopram to 2924.53 ng L−1 for O-desmethyl venlafaxine. The evolution of BOD5 and COD values were determined before and after the photocatalytic treatment. All detected pharmaceuticals were removed in percentages higher than 54% at an optimum catalyst loading ranging between 200 and 300 mg L−1. The potential of the catalyst to be reused without any treatment for two consecutive cycles was studied, showing a significant efficiency decrease.